Compact workstation from kelempayan (neolamarckia cadamba)/ Azuandi Abdullah - Abdullah, Azuandi (2014)
Furniture is a necessity that now becoming a trend from time to time in accordance with latest technology and development. There is increasingly demand for furniture that can fit small space with various functions, especially for consumers that staying at a small house, apartments, hostels or rental house. The objectives of this study were to design a compact workstation from Kelempayan (Neolamarckia cadamba) and the product should save space and multifunction. After design and manufacturing process, a survey was undertaken in evaluating the characteristic of this product. A set of questionnaires was distributed to 50 correspondents (in UiTM) based on different types of gender, profession and range of age. The characteristic that had been evaluated were such as suitability of material, compact concept, design, portability, comfortability, saving space, multifunction's, commercialization and price of product. Data recorded from survey were evaluated and it shows that different types of gender affecting the evaluation on the characteristic of the product, meanwhile there is no significant different on the evaluation based on the profession and range of age. So, it can be concluded that Kelempayan (Neolamarckia cadamba) can be a suitable material to produce this compact workstation. It also has proven as multifunction's and suitable to be used in small space. Overall, this compact workstation has great potential to be commercialized to the furniture industry in Malaysia.